Hadith #2129 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
A woman who marries on a dower or a reward or a promise before the solemnisation of marriage is entitled to it; and whatever is fixed for her after solemnisation of marriage belongs to whom it is given. A man is more entitled to receive a thing given as a gift on account of his daughter or sister (than other kinds of gifts).
Grade: Hasan

Hadith #2193 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Ata' bin Abi Rabah عطاء بن أبي رباح (Sunan Abi Dawud)
I went out with Adi ibn Adi al-Kindi till we came to Mecca. He sent me to Safiyyah daughter of Shaybah who remembered a tradition (that she had heard) from Aisha. She said: I heard Aisha say: I heard the Messenger of Allah (ﷺ) say: There is no divorce or emancipation in case of constraint or duress (ghalaq). Abu Dawud said: I think ghalaq means anger.
Grade: Hasan

Hadith #2277 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Ali ibn Abi Talib; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Nafi' b. 'Ujayr b. 'Abd Yazid b. Hashim; Ujayr bin 'Abd Yazid bin Hashim; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
While I was sitting with AbuHurayrah, a Persian woman came to him along with a son of hers. She had been divorced by her husband and they both claimed him. She said: AbuHurayrah, speaking to him in Persian, my husband wishes to take my son away. AbuHurayrah said: Cast lots for him, saying it to her in a foreign language. Then her husband came and asked: Who is disputing with me about my son? AbuHurayrah said: O Allah, I do not say this, except that I heard a woman who came to the Messenger of Al
Grade: Sahih

Hadith #2336 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
She never saw the Prophet (ﷺ) fasting the whole month except Sha’ban which he combined with Ramadan.
Grade: Sahih

Hadith #2432 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله; Umar bin Thabit عمر بن ثابت الأنصاري (Sunan Abi Dawud)
I asked or someone asked the Prophet (ﷺ) about perpetual fasting. He replied: You have a duty to your family. Fast during Ramadan and the following month, and every Wednesday and Thursday. You will then have observed a perpetual fast.
Grade: Da'if

Hadith #2712 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Umar ibn al-Khattab (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) gained booty he ordered Bilal to make a public announcement. He made a public announcement, and when the people brought their booty, he would take a fifth and divide it. Thereafter a man brought a halter of hair and said: Messenger of Allah, this is a part of the booty we got. He asked: Have you heard Bilal making announcement three times? He replied: Yes. He asked: What did prevent you from bringing it? He made some excuse, to which he said: Be (as you are), yo
Grade: Hasan

Hadith #2783 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Beware of the wages of a distributor of booty (qusamah). We asked: What is qusamah (wages of a distributor)? He said: It means a thing which is shared by the people, and then it is reduced.
Grade: Da'if

Hadith #2966 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hatm bin Isma'il al-Madni حاتم بن إسماعيل المدني; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Malik bin Aws bin al-Hadathan; Nasr bin 'Ali bin Nasr bin 'Ali; Safwan bin 'Isa al-Zhry صفوان بن عيسى الزهري أبو محمد البصري; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Usamah ibn Zayd (Sunan Abi Dawud)
‘Umar said explaining the verse: “What Allah has bestowed on His Apostle (and taken away) from them – for this ye made no expedition with either cavalry or camelry” this belonged specially to the Messenger of Allah (ﷺ): lands of ‘Urainah, Fadak, and so-and-so. What Allah as bestowed on His Apostle (and taken away) from the people of the townships – belong to Allah – to the Apostle, and to kindred and orphans, the needy and the wayfarer, to the indigent emigrants, those who were e
Grade: Sahih

Hadith #3083 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdur Rahman ibn al-Harith; al-Sa'b bin Juthama bin Qays; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Abi Dawud)
Al Sa’b bin Jaththamah reported the Apostle of Allaah(ﷺ) as saying “There is no (permission for) protected land except for Allaah and His Prophet. Ibn Shihab said “It has reached me that the Apostle of Allaah(ﷺ) protected Naqi’.”
Grade: Sahih

Hadith #3206 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Aisha bint Abi Bakr; Umarh bint 'Abdur Rahman عمرة بنت عبد الرحمن بن سعد بن زرارة (Sunan Abi Dawud)
When Uthman ibn Maz’un died, he was brought out on his bier and buried. The Prophet (ﷺ) ordered a man to bring him a stone, but he was unable to carry it. The Messenger of Allah (ﷺ) got up and going over to it rolled up his sleeves. The narrator Kathir told that al-Muttalib remarked: The one who told me about the Messenger of Allah (ﷺ) said: I still seem to see the whiteness of the forearms of the Messenger of Allah (ﷺ) when he rolled up his sleeves. He then carried it and placed it at
Grade: Hasan

Hadith #3327 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Amr bin Abi 'Amr; ibn Abbas; Ikrama عكرمة (Sunan Abi Dawud)
“Lying and swearing have a place on i.” ‘Abd Allah al-Zuhri said: “Unprofitable speech and lying.”
Grade: Sahih

Hadith #3573 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Qays Client Of 'Amr bin al-Aas أبو قيس مولى عمرو بن العاص; Amr bin al-'Aas; Basr bin Sa'id al-Madni بسر بن سعيد المدني العابد; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
The Prophet (ﷺ) said: Judges are of three types, one of whom will go to Paradise and two to Hell. The one who will go to Paradise is a man who knows what is right and gives judgment accordingly; but a man who knows what is right and acts tyrannically in his judgment will go to Hell; and a man who gives judgment for people when he is ignorant will go to Hell. Abu Dawud said: On this subject this is the soundest tradition, that is, the tradition of Ibn Buraidah: Judges are of three types.
Grade: Sahih

Hadith #3609 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Rabi'ya bin Abi 'Abdur Rahman; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
‘Amr said: In the rights (of the people).
Grade: Sahih

Hadith #3639 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin 'Abdur Rahman bin Ma'mar عبد الله بن عبد الرحمن بن معمر; Abu Sa'id al-Khudri; Amr bin Yahya bin 'Ammara عمرو بن يحيى بن عمارة; Mhmwd bin Khalid محمود بن خالد; Muhammad bin 'Uthman al-Akhnasi محمد بن عثمان الأخنسي; Yahya bin 'Ammara يحيى بن عمارة بن أبي حسن الأنصاري (Sunan Abi Dawud)
‘Amr bin Shu’aib on his father’s authority said that his grandfather told that the Messenger of Allah (ﷺ) decided regarding the stream al-Mahzur that its water should be held back till it reached the ankles, and that the upper waters should then be allowed to flow to the lower.
Grade: Hasan Sahih

Hadith #3734 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
We were with Prophet (ﷺ) and he asked for something to drink. A man from the company asked: Should we not give you nabidh (drink made from dates) to drink ? He replied : Yes . The man went quickly and bought a cup of nabidh. The Messenger of Allah (ﷺ) said: Why did you not cover it up even by putting a piece of wood on it ? Abu Dawud said: Al-Asma’i’s version has: “You put it on it…”
Grade: Sahih

Hadith #3798 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Abu Thaur al-Kalbi إبراهيم بن خالد أبو ثور الكلبي; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة (Sunan Abi Dawud)
I accompanied the Messenger of Allah (ﷺ), but I did not hear about the prohibition of (eating) insects and little creatures of land.
Grade: Da'if

Hadith #3911 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying : There is no infection, no evil, omen or serpent, in a hungry belly and no hamah. A nomadic Arab asked: How is it that when camels are in the sand as if they were gazelles and a mangy camel comes among them and it gives them mange ? He replied: Who infected the first one ? Ma’mar, quoting al-Zuhri said: A man told me that Abu Hurairah narrated to him saying that he heard the Prophet (ﷺ) say: A diseased camel should not be brought with a healthy camel t
Grade: Sahih

Hadith #4063 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; ibn Umar; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
I came to the Prophet (ﷺ) wearing a poor garment and he said (to me): Have you any property? He replied: Yes. He asked: What kind is it? He said: Allah has given me camels. Sheep, horses and slaves. He then said: When Allah gives you property, let the mark of Allah’s favour and honour to you be seen.
Grade: Sahih

Hadith #4235 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Usayd bin Abi Usayd أسيد بن أبي أسيد البراد (Sunan Abi Dawud)
The Prophet (ﷺ) got some ornaments presented by Negus as a gift to him. They contained a gold ring with an Abyssinian stone. The Messenger of Allah (ﷺ) turning his attention from it took it by means of a stick or his finger, then called Umamah, daughter of Abul’As and daughter of his daughter Zaynab, and said: Wear it, my dear daughter.
Grade: Hasan

Hadith #4331 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن (Sunan Abi Dawud)
You swear by Allah! He said: I heard Umar swearing to that in the presence of the Messenger of Allah (ﷺ), but the Messenger of Allah (ﷺ) did not make any objection to it.
Grade: Sahih

Hadith #4460 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Amr bin Abi 'Amr; ibn Abbas; Ikrama عكرمة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) made a decision about a man who had intercourse with his wife’s slave-girl as follows. If he forced her, she is free, and he shall give her mistress a slave-girl similar to her; if she asked him to have intercourse voluntarily, she will belong to him, and he shall give her mistress a slave-girl similar to her. Abu Dawud said: This tradition has been transmitted by Yunus b. ‘Ubaid, ‘Amr b. Dinar, Mansur b. Zadhan and Salam from al-Hasan to the same effect. But y
Grade: Hasan

Hadith #4462 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Amr bin Abi 'Amr; ibn Abbas; Ikrama عكرمة (Sunan Abi Dawud)
The Prophet (ﷺ) said: If you find anyone doing as Lot’s people did, kill the one who does it, and the one to whom it is done. Abu Dawud said: A similar tradition has also been transmitted by Sulaiman b. Bilal from ‘Amr b. Abi ‘Umar. And ‘Abbad b. Mansur transmitted it from ‘Ikrimah on the authority of Ibn ‘Abbas who transmitted it from the Prophet (ﷺ). It has also been transmitted by Ibn Juraij from Ibrahim from Dawud b. Al-Husain from ‘Ikrimah on the authority of Ibn ‘Abbas
Grade: Hasan Sahih

Hadith #4530 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'd ibn 'Ubadah (Sunan Abi Dawud)
I and Ashtar went to Ali and said to him: Did the Messenger of Allah (ﷺ) give you any instruction about anything for which he did not give any instruction to the people in general? He said: No, except what is contained in this document of mine. Musaddad said: He then took out a document. Ahmad said: A document from the sheath of his sword. It contained: The lives of all Muslims are equal; they are one hand against others; the lowliest of them can guarantee their protection. Beware, a Muslim mu
Grade: Sahih

Hadith #4813 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Sa'id al-Khudri; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The Prophet (ﷺ) said: If someone is given something, he should give a return for it provided he can afford; if he cannot afford, he should praise him. He who praises him for it, thanks him, and he who conceals it is ungrateful to him. Abu Dawud said: It has been transmitted by Yahya b. Ayyub, from `Umarah b. Ghaziyyah, from Sharahbil on the authority of Jabir. Abu Dawud said: In the chain of this tradition `Umarah b. Ghaziyyah said: A man from my tribe said. The man referred by him is Sharahbi
Grade: Hasan

Hadith #4872 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن (Sunan Abi Dawud)
The worst of the people is a man who is double-faced; he presents one face to some and another to others.
Grade: Sahih

Hadith #4892 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن (Sunan Abi Dawud)
AbulHaytham quoted Dukhayn, the scribe of Uqbah ibn Amir, saying: We had some neighbours who used to drink wine. I forbade them, but they did not stop. I then said to Uqbah ibn Amir: These neighbours of ours drink wine, and I tried to prevent them but they did not stop, and I am going to call the police about them. He said: Leave them. I again came to Uqbah ibn Amir and said: Our neighbours have refused to refrain from drinking wine, and I am going to call the police for them. He said: Woe to th
Grade: Hasan

Hadith #5062 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
Fatimah complained to the Prophet (May peace be upon him) of the effect of the grinding stone on her hand. Then some slaves (prisoners of war) were brought to him. So she went to him to ask for (one of) them, but she did not find him. She mentioned the matter to ‘A’ishah. When the prophet (May peace be upon him) came, she informed him. He (the prophet) visited us (Ali) when we had gone to bed, and when we were about to get up, he said: stay where you are. He then came and sat down between us
Grade: Sahih

Hadith #5099 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Salah bin Kaysan al-Madni صالح بن كيسان المدني أبو محمد; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود; Zayd bin Khalid al-Juhni (Sunan Abi Dawud)
When the Prophet (ﷺ) saw a cloud formation in the sky, he left work, even if he were at prayer, and then would say: “O Allah! I seek refuge in Thee from its evil. ” If it rained, he would say: “O Allah! send a beneficial downpour.”
Grade: Sahih

Hadith #5190 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Amr bin Abi 'Amr; Ikrama عكرمة (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of you is invited to take meals and comes along with the messenger, that serves as permission for him to enter. Abu ‘Ali al-Lu’lu said: I heard Abu Dawud say: Qatadah did not hear anything from Abu Rafi’.
Grade: Sahih

Hadith #5270 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Usayd Malik bin Rabi'a; al-Hakm bin Nafi', Abu al-Yaman الحكم بن نافع أبو اليمان الحمصي; Hamza bin Abi Usayd al-Sa'idi; Shdad bin Abi 'Amr شداد بن أبي عمرو بن حماس (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) prohibited throwing pebbles (in sport) saying : game is not caught by such means. Neither is an enemy injured, but it may sometimes put out an eye or break a tooth.
Grade: Sahih